1.1k views
5 votes

-3/z+7/4z=5/z-25

2 Answers

2 votes

Answer:

z = 5

Explanation:

simplify

5/(z-25) first

turning it into

((0 - 3/z) + 7/4z) - 5/(z - 25) = 0

then simplify 7/4z

((0 - 3/z) + 7/4z) - 5/(z-25) = 0

when the fractions denominator is 0 then the numerator must be 0

turning the equation into

-25 * (z - 5) = 0

solve

-25 = 0

something that is not zero cannot equal zero.

z - 5 = 0

5 - 5 = 0

z = 5

hope this helps:)

User Rli
by
5.2k points
5 votes

Answer:

z = 1/4

Explanation:

See attached image

-3/z+7/4z=5/z-25-example-1
User PseudoAj
by
4.9k points